Preliminary Efficacy of Positive Change(+Change): A Pilot Randomized Controlled Trial of an Integrated Alcohol and Sexual Assault Prevention Program Tailored by Gender and Sexual Orientation - Gilmore, Amanda K. (Journal of interpersonal violence, 2025)
The current study presents preliminary efficacy findings of a pilot randomized controlled trial of Positive Change© (+Change© ). +Change© utilizes personalized normative feedback to target alcohol use, sexual assault (SA) victimization, SA perpetration, and bystander intervention tailored for heterosexual cisgender men, heterosexual cisgender women, and sexual and gender-minoritized (SGM) groups. Participants included 165 undergraduate students aged 18 to 25 years old from a large public university in the Southwestern U.S. who engaged in past month heavy episodic drinking. Participants (57 cisgender heterosexual men; 54 cisgender heterosexual women; and 54 SGM) were randomized to +Change© (n = 83) or an assessment-only control (n = 82) and completed surveys online at baseline and 3-month follow-up in a parallel design with a 1:1 ratio (NCT04089137). The current study presents the secondary outcomes of the pilot randomized controlled trial which include alcohol use, SA victimization, SA perpetration, and bystander intervention behavior. +Change© was associated with significantly less severe SA victimization and more bystander intervention behavior at 3-month follow-up relative to the control. There were no significant differences between conditions in alcohol use at 3-month follow-up, however, the magnitude of decreases in drinking in the +Change© condition in this pilot study were consistent with other personalized normative feedback interventions. The present study was unable to assess differences in SA perpetration due to low base rates. No adverse effects among those receiving the intervention were observed. Findings suggested that +Change© may be a feasible strategy to prevent SA, by reducing student SA victimization and increasing bystander intervention. A fully powered randomized clinical trial is needed to examine the effects of +Change©.